2021
DOI: 10.3390/atmos12091185
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity in Tradescantia pallida as an Indicator of the Effect of Air Pollution and Human Health

Abstract: The present study aims to relate the micronucleus frequency in Tradescantia pallida to environmental factors and cardiorespiratory diseases to infer the effect of air pollution. The number of hospitalizations, diseases cases, frequency of micronuclei in plants, environmental variables, altitude, and vehicle traffic in cities of Mato Grosso do Sul were evaluated due to the high flow that surrounds agribusiness. The frequency of micronuclei decreased with the increase in relative humidity, while the altitude did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…In a study on the influence of pollutants on T. pallida, the authors [27,29] identified a positive association between genetic effects in pollen grains of inflorescences exposed to a high volume of cars in urban intersections. Similar results were found in regions with different fleet volumes in the municipalities of Ribeirão Preto in southeastern Brazil [36] and São Leopoldo in southern Brazil [58] and in the Dourados microregion in central-western Brazil [23], where areas with high vehicle emissions were correlated to higher frequencies of MCN. These regions have minimum and maximum distances from each other of approximately 900 and 1400 km, respectively; however, they showed consistent patterns when inferring vehicle flow at the MCN frequency.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In a study on the influence of pollutants on T. pallida, the authors [27,29] identified a positive association between genetic effects in pollen grains of inflorescences exposed to a high volume of cars in urban intersections. Similar results were found in regions with different fleet volumes in the municipalities of Ribeirão Preto in southeastern Brazil [36] and São Leopoldo in southern Brazil [58] and in the Dourados microregion in central-western Brazil [23], where areas with high vehicle emissions were correlated to higher frequencies of MCN. These regions have minimum and maximum distances from each other of approximately 900 and 1400 km, respectively; however, they showed consistent patterns when inferring vehicle flow at the MCN frequency.…”
Section: Discussionsupporting
confidence: 83%
“…Angélica has a single-access road to the municipality, which results in reduced vehicle circulation and consequently minimal emissions of exhaust gases from the combustion engine with a high concentration of toxic elements. Godoy et al [23] also showed that the high MCN frequencies in T. pallida were mainly related to the high vehicle flow and high population density.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations